Pengembangan Media Flashcard Digital Berbasis Augmented Reality dalam Pembelajaran Bahasa Indonesia Kelas IV Sekolah Dasar - Nonik Eva Harijati; Adlia Alfi Riani; Dina Ramadhanti (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study aimed to develop an Augmented Reality  (AR)-based digital flashcard medium that is valid, practical, and effective in supporting digital literacy in Indonesian language learning for fourth-grade students at SD IBBS Tulungagung. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants included media experts, material experts, fourth-grade teachers, and 18 fourth-grade students. Data were collected through validation questionnaires, practicality questionnaires, and digital literacy Pretest–Posttest assessments. Data were analyzed using descriptive quantitative techniques through percentage scores and N-Gain  analysis. The results showed that the developed medium achieved a validity score of 89.75% and a practicality score of 89.75%, both categorized as very feasible and very practical, respectively. Furthermore, the effectiveness test yielded an N-Gain  score of 0.65, indicating a moderate level of effectiveness in improving students’ digital literacy. Therefore, the AR-based digital flashcard medium is suitable for use as an interactive learning medium in Indonesian language instruction and can support the enhancement of digital literacy among elementary school students.